2017
DOI: 10.1016/j.ultsonch.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new paradigm for sonochemistry: Short review on nonequilibrium plasma observations by means of MBSL spectroscopy in aqueous solutions

Abstract: This review summarizes recent studies of multibubble sonoluminescence (MBSL) in aqueous media in order to highlight new insights into the origin of the sonochemical activity. The observation of OH(CΣ-AΣ) emission band and a spectroscopic analysis of OH(AΣ-XΠ) emission band in MBSL of water pre-equilibrated with noble gases revealed the formation of a nonequilibrium plasma inside the collapsing bubble (T>T>T, where T is an electron temperature, T is a vibrational temperature and T is a rotational (gas) temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 50 publications
0
25
0
1
Order By: Relevance
“…Recent spectroscopic studies have shown a more complex situation with non-equilibrium plasma formation in the form of excited •OH radicals in different energy states [80]. In this instance the electron temperature (T e ) is much greater than the vibrational (T v ), rotational (T r ) and translational (T g ) temperatures in the order T e > T v > T r ≈ T g [81].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent spectroscopic studies have shown a more complex situation with non-equilibrium plasma formation in the form of excited •OH radicals in different energy states [80]. In this instance the electron temperature (T e ) is much greater than the vibrational (T v ), rotational (T r ) and translational (T g ) temperatures in the order T e > T v > T r ≈ T g [81].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Spectral emissions from multibubble sonoluminescence in argon atmosphere have shown that vibrational excitations of the plasma inside the bubble can change with frequency [81]. A disparity in the population of vibrational levels can have significant effects on the reactions taking place for several sonochemical systems [80]. As frequency is increased bubbles experience a shorter growth time and sonochemical yield decreases as observed between 585 and 1140 kHz [106].…”
Section: Frequencymentioning
confidence: 99%
“…In aqueous solutions, cavitation causes splitting of water molecules leading to formation of OH % radicals and H atoms, and to the products of their mutual recombination: H 2 O 2 and H 2 , respectively [11]. Recent spectroscopic studies of light emitted by collapsing bubbles, called sonoluminescence, revealed formation of nonequilibrium plasma inside the bubble [12]. Therefore, each cavitation bubble can be considered as microscopic plasma reactor producing highly reactive species in liquids at almost room bulk temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Auch die Frage, was da genau strahlt, ist weiterhin aktueller Forschungsgegenstand. So zeigen zum Beispiel neuere Untersuchungen an Emissionslinien unterschiedliche Temperaturen von Elektronen und Ionen im Sonolumineszenz‐Plasma , und es wurde von unerwartet hoch ionisiertem Plasma in speziellen Einzelblasen‐Experimenten berichtet . Es gibt auch Hinweise, dass es womöglich einen sehr heißen Kern im Innern des Hot Spots geben könnte, den man aber nicht sehen kann – die beobachteten Temperaturen würden dann nur von der Oberfläche stammen, ähnlich wie bei der Sonne.…”
Section: Blasendynamik In Blasenwolkenunclassified